Peran Program Pengembangan Petani Sebagai Implementasi CSR PT. SMGP terhadap Resistensi Masyarakat - Taufik, Ahmad; Lestari, Indra (UI Scholars Hub, 2023)
The presence of mining projects or power plants that utilize or exploit natural resources has the potential for environmental, social, and economic problems for the community. There are many cases of rejection from communities around the project area, which can even lead to conflict and anarchic actions that cause losses for several parties. Meanwhile, there are demands for energy sustainability amidst the current crisis in the availability of fossil energy. Therefore, the government provides support through several policies, one of which is encouraging the implementation of Corporate Social Responsibility so that core project activities can take place with attention to the welfare of the surrounding community. Using qualitative methods and data collection techniques through interviews and documentation studies, this article contains a description and analysis of the role of farmer development programs as PT CSR. SMGP in the face of community resistance. The results show that the farmer development program as a CSR of PT. SMGP is effective in directly reducing farmer resistance. The CSR program indirectly provides a sense of the company's presence in nearby village communities so that the continuity of the company's activities is supported (social license to operate). Apart from that, field findings also illustrate the forms and reasons for community resistance to companies.